Transforming teaching and learning conditions at selected universities in the Eastern Cape, South Africa - Cishe, Elphinah Nomabandla; Linake, Manthekeleng Agnes; Nongalo, Noloyiso; Nqabeni, Pelokazi (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Eastern Cape Universities have different Teaching and Learning Conditions, which need to be transformed. This paper explored the extent to which teaching and learning conditions are transformed in selected universities in the Eastern Cape Province, South Africa. The focus was on the perspectives of students and lecturers on transforming teaching and learning conditions in the Faculties of Education in two selected universities. Thus, this paper covers the improvement of the quality of teaching and learning throughout the system and advancing redress for past inequalities. The theory of transformation underpinned the paper. The positivism paradigm, quantitative research approach, and survey design were adopted whereby the questionnaires were used to collect data. Systematic sampling was used to select 31 lectures and 106 students. Data were analysed using Statistical Package for Social Sciences (SPSS) to compile appropriate frequency tables and graphs. The findings of the study revealed that positive strides have been made to ensure gender and age balances in student enrolment at higher education institutions in the Eastern Cape Province of South Africa, and universities in the Eastern Cape have gradually transformed to provide quality programs leading to institutional effectiveness and efficiency. It can be concluded that pedagogy considers what students already know and that leads to developing strategies that can be used in transforming teaching and learning. The study recommends that higher education institutions should ensure that age, gender and race balances should be considered in student enrolment, as this will ensure that there are equitable teaching and learning conditions.